The Authority Of The Executive Officer As A Curator For The Management Of Confiscated Assets/Evidence In The Framework Of Restoring The Rights Of Criminal Acts Victims In The Form Of Restitution - Radityo Wisnu Aji (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2026)
The Public Prosecutor (Prosecutor), as an executive officer, holds constitutional authority to execute court decisions that have obtained permanent legal force. In practice, however, prosecutors frequently encounter juridical challenges when court rulings order the management, auction, and distribution of seized assets or evidentiary goods for the purpose of restoring victims’ rights, including compensation, restitution, and rehabilitation. These challenges arise primarily due to the absence of clear normative regulations governing the legal basis and procedural mechanisms for prosecutors to exercise such authority as executors. This issue becomes increasingly complex when judicial legal reasoning (legal finding) results in progressive decisions that are not supported by adequate implementing regulations. This article aims to analyze the ideal scope of prosecutorial authority as an executive officer in managing seized assets and to formulate an ideal model for asset administration and liquidation oriented toward the recovery of victims’ rights in criminal cases. The research employs a normative legal research method using statutory, conceptual, and case study approaches, particularly examining Decision of the Banjarmasin District Court Number 343/Pid.Sus/2022/PN.Bjm. The findings indicate a regulatory vacuum and normative disharmony between statutory laws, Supreme Court regulations, and internal prosecutorial guidelines, which hinder the effective restoration of victims’ rights. Therefore, strengthening prosecutorial authority in conducting asset tracing, execution seizure, and asset liquidation is necessary by adopting principles of bankruptcy trusteeship (curatorship), implemented in a proportional, transparent, and accountable manner. This model is expected to promote restorative justice, ensure legal certainty, and enhance legal utility for victims of criminal offenses.